A comparative study of integrated FMCDM methods for evaluation of organizational strategy development - Yapici Pehlivan, Nimet; Şahin, Aynur; Zavadskas, Edmundas Kazimieras; Turskis, Zenonas (Journal of Business Economics and Management, 2018)
With the globalization of economy and development of technology, organizational strategy development in distribution channel management has become more significant for competitive business world. To improve distribution channel performance, many companies have focused on Multi-Criteria Decision Making (MCDM) methods. In the literature, there are a great number of studies on MCDM and fuzzy MCDM (FMCDM) methods, whereas a few studies on integrated FMCDM methods. The purpose of this study is to propose integrated FMCDM methodology including FAHP, WASPAS-F, EDAS-F and ARAS-F. In these methods, relative importances of the criteria are determined by FAHP. Managerial and financial perspective is determined as the most important criteria by FAHP methods. Then WASPAS-F, EDAS-F and ARAS-F methods are carried out to rank the alternatives. The practical implication of the integrated FMCDM methods is the use of linguistic variables for assessment of the criteria and the alternatives. As a research implication, Hybrid Based Strategy is determined as the best organizational strategy. The originality and value of study is to present comparative analyzes using the newly developed WASPAS-F, EDAS-F and ARAS-F integrated with FAHP methods. An important finding of the study is that the ranking results of the proposed methods are consistent with each other.